(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In the fields of agriculture and healthcare, the usage of two very common prominent and emerging technical knowledge, Cloud Computing i.e., CC in short and the Internet of Things or IoT in short, is currently a trending topic. Motivated by a desire to create a more ecological world, the authors in the paper examines a number of technological aspects and concerns related to eco-friendly CC and IoT, and expands on the argument by examining the fall of electric power intake of the two listed techniques when used together either in farm or health related work. It will be addressed in the paper - the idea of the ecological ICTs (Information and Communications Technologies) and its past that are responsible for empowering Green-IoT. Eco-friendly or green computing is introduced initially, followed by a discussion of current research on the discussed two very fast developing knowledges in farming and medical care. Furthermore, this article adds by proposing a sensor cloud integration paradigm for Green-IoT Healthcare and Agriculture Application (GHAA). Finally, the benefits, difficulties, and future research prospects for green